PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI FUNGSI DI KELAS XI SMA KRISTEN 2 TOMOHON - Kellah, Zefanya; Pitoy, Cory; Jannah, Miftahul (LPPM Politeknik Saint Paul Sorong, 2024)
This study aims to identify whether the average learning outcomes of students who learn using the Problem Based Learning learning model are higher than the average learning outcomes of students who learn using the Direct learning model on Function material. This research is a study that uses a posttest-only control group design. The population of this study were all grade XI students and the samples in this study were grade XI-1 as an experimental class consisting of 25 students and grade XI-2 as a control class consisting of 25 students at SMA Kristen 2 Tomohon in the 2024/2025 school year. The results revealed that there was a difference in the average learning outcomes of students taught using the Problem Based Learning model with students taught using the Direct learning model. Based on the above results, it is concluded that learning by using the Problem Based Learning learning model can improve students' mathematics learning outcomes on function material.